Superelastic, Macroporous Polystyrene‐Mediated Graphene Aerogels for Active Pressure Sensing. Issue 7 (25th February 2016) - Zhang, Panpan; Lv, Lingxiao; Cheng, Zhihua; Liang, Yuan; Zhou, Qinhan; Zhao, Yang; Qu, Liangti
Abstract: Three‐dimensional (3D) graphene‐based polymer/graphene aerogels with excellent mechanical properties are crucial for broad applications. The creation of such polymer/graphene aerogels remains challenging because of the poor dispersion and compatibility of polymer within the graphene matrix. By using the freezing‐directed assembly of graphene under the assistance of surfactant, 3D macroporous polystyrene/graphene aerogels (MPS‐GAs) with lightweight, superelastivity (80 % strain), high strength (80 kPa), and good electrical properties have been achieved in this study. The as‐prepared MPS‐GAs shows excellent electromechanical performance with stable cyclic resilient properties and sensitive resistance responses, thus making the MPS‐GAs promising candidates for applications in actuators, elastic conductors, strain/pressure sensors, and wearable devices. Abstract : Under pressure : 3D macroporous polystyrene/graphene aerogels (MPS‐GAs) with lightweight, superelastivity (80 % strain), high strength (80 kPa), and good electrical properties have been achieved. The MPS‐GAs show excellent electromechanical performance with stable cyclic resilient properties and sensitive resistance responses.